PENGAKUAN DAN PERLINDUNGAN HUKUM TERHADAP HAK-HAK TRADISIONAL MASYARAKAT HUKUM ADAT DAYAK MA’ANYAN DI KECAMATAN AWANG KABUPATEN BARITO TIMUR - Mutia Evi Kristhy; Harry; Suriansyah murhaini; Thea Farina; Heriamariaty; Sangking Mahar; Kiki Kristanto (Jurnal Komunikasi Hukum, 2022)
The purpose of this research is to study and analyze The Traditional Rights of the Ma’anyan Dayak Indigenous Society in Awang Sub Regency East Barito Regency which has not yet acquired recognition and protection and Analyzing The Legal Recognition and Protection of the Ma’anyan Dayak Indigenous Law Society when there is an event of legal actions occurs. This Research is Empirical Research which obtained through legal identification (Oral) in form of habits that are still valid in the Ma’ayan Dayak Indigenous Society unit in Awang Sub Regency East Barito Regency which is then analyzed using an objective and relevant theory about The Traditional Rights Indigenous Law Society, therefore accurate results can be discovered about types of rights analyze The Traditional Rights of the Ma’anyan Dayak Indigenous Society in Awang Sub Regency East Barito Regency which must be given recognition and protection. This Research concludes that The Traditional Rights of the Ma’anyan Dayak Indigenous Society in Awang Sub Regency have not been protected since the regional government of east barito regency until now has not implemented and follow up The Minister of Affairs Regulation Number 52 of 2014 and from the Decree the Governor of Central Kalimantan Number 188.44/360/2020 about establishment the Central Kalimantan Province. Legally, there has been legal recognition of the indigenous law society and traditional rights attached to The Traditional Rights of the Ma’anyan Dayak Indigenous Society in Awang Sub Regency, which is Article 18 B paragraph (1) of the 1945 Constitution, however, there has not been further regulated in form of legislation and the desired legal recognition is not just de jure, limited to limited verbal legal recognition which coming first from the indigenous society itself and the surrounding society, but demand on embodiment in the true sense. Therefore when there is an event of legal actions occurring over The Traditional Rights of the Ma’anyan Dayak Indigenous Society prefers to resolve legal actions outside the court with their mechanism to resolve legal actions that occur in their territory according to the customary law through deliberation and consensus. Therefore, the Regional Government of East Barito Regency is expected to form a regional regulation as legal protection for protecting the rights of indigenous society in the various development process, the rights of indigenous society are not ignored.